Lack of variation in venous tone potentiates vasovagal syncope. Issue 6 (June 1992) - Hargreaves, A D; Muir, A L
Abstract : OBJECTIVE--To investigate the peripheral venous response to head up tilting in malignant vasovagal syndrome. PATIENTS--31 Patients with unexplained syncope or dizziness referred from the cardiology department. METHODS--Changes in calf venous volume were studied by a radionuclide technique during 45 degrees head up tilt testing. RESULTS--During tilt testing six patients became syncopal but 25 were symptom free. The syncopal group had greater increases in calf venous volume after the change in posture and perhaps more importantly considerably less variability in the venous volume during the tilted period. CONCLUSIONS--The venous response was different in the syncopal patients. The lack of response of the peripheral venous circulation to changes in the central circulation may be responsible for triggering the Bezold-Jarisch reflex and malignant vasovagal syncope.